The Influence of Indo-Pacific Economic Framework on Peace Stability in The ASEAN Region - Abadi, Fany Anggun; Al-Fadhat, Faris (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2023)
By taking into account all motives for foreign economic cooperation, including the Indo-Pacific Economics Framework (IPEF), this framework will definitely affect the economies of several countries in the region, especially Southeast Asia. ASEAN is demanded not only as an elite state organization but furthermore, is also required to have the capability to involve all elements of its member countries' societies, in the varying fields, especially economic, political and peace stability. This paper then raised a question regarding how does the IPEF influence the peace stability in the ASEAN Region. In examining this question, the author used the theory of international organizations typology, international economic regime theory, and regional peace stability theory. It is concluded that the step that's certainly must be taken by countries in the region is to help each other. Thus, it is the joint responsibility of each country, both inside and outside the region to prevent the emergence of conflict and voluntarily build trust to achieve regional stability. In this context, ASEAN certainly must be stronger. Keywords: ASEAN, economy, stability Dengan memperhitungkan segala motif kerja sama ekonomi luar negeri, termasuk Indo-Pacific Economic Framework (IPEF), kerangka ini pasti akan berpengaruh terhadap perekonomian beberapa negara di kawasan, khususnya Asia Tenggara. ASEAN dituntut tidak hanya sebagai organisasi elit negara, tetapi juga dituntut untuk memiliki kapabilitas untuk melibatkan seluruh elemen masyarakat negara anggotanya dalam berbagai bidang, terutama ekonomi, politik, dan stabilitas perdamaian. Penelitian ini kemudian mengajukan pertanyaan terkait bagaimana pengaruh Indo-Pacific Economic Framework (IPEF) terhadap stabilitas perdamaian di kawasan ASEAN. Dalam menganalisis pertanyaan ini, penulis menggunakan teori tipologi organisasi internasional, teori rezim ekonomi internasional, dan teori stabilitas perdamaian regional. Dapat disimpulkan bahwa langkah yang pastinya harus diambil oleh negara-negara di kawasan adalah saling membantu. Dengan demikian, menjadi tanggung jawab bersama negara-negara, baik di dalam maupun di luar kawasan untuk mencegah konflik dan membangun kepercayaan secara sukarela untuk mencapai stabilitas kawasan. Dalam konteks ini, tentunya ASEAN harus semakin kuat. Kata-kata Kunci: ASEAN, ekonomi, stabilitas